IgG antibodies levels in blood serum of workers exposed to microbial contaminants of metal working fluids - Jabbar, Mohammed Abdulrazzaq; Hashim, Zailina; Awang Hamat, Rukman; Zainuddin, Huda (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Water-based metalworking fluid (MWF) provides a suitable environment for microbes to grow. This study aimed at identifying the level and species of microbial contamination of MWF in a metal machining factory and to determine the corresponding Immunoglobulin G (IgG) levels in the workers’ blood samples. Methods: Total of 298 workers in the production section of a metal machining factory, the production section using MWF as coolant fluid, were involved in this study. The Analytical Profile Index system was used to identify the species of microbes isolated from MWF bulk and air samples. Tryptone soya agar was used to incubate unknown bacteria, and sabouraud dextrose agar was used for unknown fungi. The level of IgG antibodies in workers’ blood were measured as an indicator of the exposure to the microbes isolated from MWF, corresponded to the microbial species isolated from MWF. Results: The most dominant microbes isolated from the channels were Candida albicans, Klebsiella pneumoniae, E. coli and Pseudomonas aeruginosa. A total of 21 (34.4%) workers were positively exposed to E. coli, 30 (42.2%) to Pseudomonas aeruginosa, and 45(75%) exposed to Candida albicans. Also, the mean level of optic density of IgG to Klebsiella pneumoniae was 0.415 (0.02). Conclusion: Water-based metalworking fluid in this metal machining factory was contaminated with bacteria and fungi. The workers in the production section were exposed to MWF as well as the microbes present in MWF. The level of IgG in blood was the biomarkers for occupational exposure to microbial contaminant MWF.